Dice, sticks, pixels and bits: didactic alternatives to explore the methodology of Monte Carlo in a ludic tone - Navone, Hugo D. (2013)
This paper presents didactic strategies in a ludic tone to explore the methodology of Monte Carlo and analizes the implementations that have been performed in several educational scenarios. These proposals allow us to put into action concepts of probability and statistics in an amusing and attractive way by conducting cooperative “experiments-games” that are based on the use of real and virtual objects. Each strategy is aimed to teachers of high school and teacher training institutes, and also for early stages at University level, in order to be modified, recreated, and enhanced according to the specific areas of application.